The Internet as a Reactualization of the Dakwah Communication System in the Digita Era - Astri Dwi Andriani; Aminah Agustinah (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This research aims to determine descriptive knowledge regarding the role of the internet as a re-actualization of the da'wah communication system in the digital era. The type of research used in this discussion is using library research or literature review which includes: systematic identification, and analysis of documents containing information related to the study problem. The research results show that the Internet has become an integral part of people's lives in the digital era. With the internet, the barriers of distance and time that used to be obstacles are now starting to fade. The new media era provides open opportunities in the process of transformation of Islamic da'wah. The use of the internet as a new media is accompanied by the creativity and innovation of preachers in using digital spaces for the continuation of Islamic da'wah. This can be seen from the emergence of cyber da'wah discourse, the development of online Islamic literature, and Amar Ma'ruf Nahi Munkar's activities in the digital realm.